2021
DOI: 10.3892/mmr.2021.11945
|View full text |Cite|
|
Sign up to set email alerts
|

20(s)‑ginseonside‑Rg3 modulation of AMPK/FoxO3 signaling to attenuate mitochondrial dysfunction in a dexamethasone‑injured C2C12 myotube‑based model of skeletal atrophy in vitro

Abstract: Muscle atrophy, a side effect from administration of the anti-inflammatory medication dexamethasone (DEX), is preventable by concomitant administration of the major monomeric constituent of Panax ginseng C.A. Meyer, 20(S)-ginsenoside Rg3 (S-Rg3). Putative S-Rg3-associated prevention of DEX-induced muscle atrophy may involve S-Rg3 mitigation of DEX-induced mitochondrial dysfunction. In the present study, MTT assays revealed enhanced cell viability following S-Rg3 treatment of DEX-injured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…FoxO3a is involved in the regulation of mitochondrial function and energy homeostasis [ 20 , 21 ]. Previous studies found that mitochondrial dysfunction resulted in insufficient ATP supply and activation of the AMPK/FoxO3a pathway [ 22 , 23 ]. However, whether FoxO3a mediates mitochondrial activity in regulating ferroptosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…FoxO3a is involved in the regulation of mitochondrial function and energy homeostasis [ 20 , 21 ]. Previous studies found that mitochondrial dysfunction resulted in insufficient ATP supply and activation of the AMPK/FoxO3a pathway [ 22 , 23 ]. However, whether FoxO3a mediates mitochondrial activity in regulating ferroptosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…BAX, acting as a pro-apoptotic protein, mediates cell death through mitochondrial permeability transition induction, while Bcl-2, an anti-apoptotic protein, suppresses apoptosis by inhibiting BAX activity [ 56 ]. Several studies have shown increased apoptosis in DEX-treated C2C12 myotubes or mice, with co-treatment with natural compounds like quercetin, myricanol, fucoxanthin, and 20( S )-ginseonside-Rg3 preventing apoptosis by reducing BAX expression and increasing Bcl-2 expression [ 37 , 38 , 39 , 57 ]. Our current study confirmed these findings by observing increased BAX expression and decreased Bcl-2 expression in DEX-treated C2C12 myotubes, both of which were significantly inhibited by LRCE treatment ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, if AMPK is activated, as in the response to low glucose levels or to energetic stress, it induces autophagy [ 99 ]. Indeed, when activated, AMPK inhibits mTORC1, stimulates ULK1 kinase through phosphorylation of ULK1Ser317 and Sr777 [ 98 ] and Ser555 [ 100 ], as well as triggers FOXO3, upregulating the expression of muscle specific atrophy-induced genes [ 101 , 102 ]. In particular, this excessive dysregulated event in skeletal muscle can culminate in protein degradation, and thus determines atrophy [ 103 ].…”
Section: Autophagy In Osteosarcopeniamentioning
confidence: 99%